Prediction of wireless sensor network signal attenuation in plantation environment - Liu Hua; Zhang Junguo; Lin Fantao (Institute of Advanced Engineering and Science, 2014)
Because of wireless sensor network signal attenuation phenomena in the process of transmission in plantation environment, mastering the law of 2.4GHz wireless sensor network signal attenuation in plantation environment has become a key to the rational distribution of wireless sensor networks in the forest. In this paper, an intelligent forecasting method using wavelet and regression analysis approach is presented of prediction of 2.4GHz wireless sensor network signal attenuation in plantation environment. By using wavelet decomposition on the average field strength values in plantation environment, the characteristics in the wavelet scale sequences can be recognized. And by using simple linear regression analysis, the decomposed data can be predicted. Then data after regression analysis can be used in wavelet reconstruction. Finally, the obtained results will be compared with the other average field strength values. The comparison shows that this wavelet and regression analysis method is effective to the prediction of 2.4GHz wireless sensor network signal attenuation. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4429